Educational systems in the context of the transition from New Public Management to the Post-New Public Management: comparative study between Brazil and Spain - Parente, Juliano Mota [UNESP]; Espejo Villar, Lourdes Belen (Editora Univ Federal Parana, Centro Politecnico, 2020)
The purpose of this article is to systematize the transition from New Public Management (NGP) to Post-New Public Management (PNGP), verifying the extent to which these models have currently influenced the educational systems of Brazil and Spain. From the reforms in public administration and educational management that took place after the 1990s, we can observe the implementation of public policies based on NGP and PNGP, strengthening the discourse of world institutionalism and global ideologies that defend a supranational and regulatory state of a standardized educational system. In this context, our object of study focuses on public education in Brazil and Spain, analyzing the interferences in the field of educational policy and management. Methodologically, the work was built upon a comparative perspective of the educational systems of Brazil and Spain, following the formal approach (PEGORARO, 2010) and the theory of international economics (COHEN, 2008). The analyzed data allowed us to refer to the influence of NGP and PNGP in the educational systems of the countries studied, legitimizing a trend of global educational rationality.
Keywords: Education; Post-New Public Management; Educational systems; Educational management